2018
DOI: 10.1590/0102-311x00194717
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de vacinação contra gripe nas populações adulta e idosa com doença respiratória pulmonar crônica

Abstract: The objective was to estimate the prevalence of influenza vaccination in adults and elderly with chronic respiratory diseases (CRDs). The sample included individuals 20 to 59 years of age (n = 23,329) and ≥ 60 years (n = 9,019) that participated in the Brazilian National Survey on Access, Utilization, and Promotion of Rational Use of Medicines (PNAUM) in 2013-2014. We estimated influenza vaccination prevalence rates and respective 95% confidence intervals (95%CI). Associations were verified with the Rao-Scott … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
(19 reference statements)
1
1
0
5
Order By: Relevance
“…17,24,25 We found, unlike other studies, that females were less likely to uptake the vaccine than males. 6,17,19 However other studies, some performed in Spain, showed similar results to ours. 7,10,26 In our opinion, this could be explained by a lack of recommendation for females, as they are considered to be more aware of self health care and prevention compliance habits.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…17,24,25 We found, unlike other studies, that females were less likely to uptake the vaccine than males. 6,17,19 However other studies, some performed in Spain, showed similar results to ours. 7,10,26 In our opinion, this could be explained by a lack of recommendation for females, as they are considered to be more aware of self health care and prevention compliance habits.…”
supporting
confidence: 91%
“…10 Reports from other countries found results ranging from 37.4% to 49,1% uptake among patients with respiratory disease, which are considered low vaccination rates and agree with us finding higher vaccination uptake among elder persons. 13,19 This could be explained because most patients and physicians are more self-aware of pneumonia as the most severe complication of influenza disease among older patients and vaccination is known to be effective to prevent hospitalizations. 14,20 Regarding vaccination coverage among the cancer group patients, we observed the lowest rate, with 34.9% and this remains low for young or old patients.…”
mentioning
confidence: 99%
“…La Organización Mundial de la Salud y las guías Global Initiative for Chronic Obstructive Lung Disease (GOLD) recomiendan la inmunización contra el virus de la gripe en los pacientes EPOC en periodo gripal 10 , 11 , 12 . La vacuna antigripal ha demostrado reducir el número de exacerbaciones y muertes en pacientes EPOC 13 .…”
Section: Introductionunclassified
“…A infecção pelo vírus Influenza pode frequentemente causar complicações, sendo a pneumonia a principal complicação relacionada à casos de hospitalizações e até o óbito. Não obstante, a infecção pelo vírus ainda pode ocasionar a exacerbação de doenças crônicas como a doença pulmonar obstrutiva crônica (DPOC), cardiopatias, dentre outras (BACURAU, 2018).…”
Section: Introductionunclassified
“…Atualmente, a forma mais eficaz de prevenção contra o vírus da Influenza e de suas complicações é feita por meio da imunização, onde no Brasil foi estabelecida por meio de campanhas, tendo início no ano de 1999 e repercutindo de forma positiva na redução de complicações, hospitalizações e gastos excessivos com medicamentos e mortes evitáveis até então (BACURAU, 2018).…”
Section: Introductionunclassified